2017
DOI: 10.1039/c7ra06351b
|View full text |Cite
|
Sign up to set email alerts
|

Development of organic–inorganic hybrid beads from sepiolite and cellulose for effective adsorption of malachite green

Abstract: A facile approach has been developed to fabricate well defined organic–inorganic hybrid beads from widely available bamboo pulp and sepiolite, in expectation of an alternative green adsorbent for the removal of organic dyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 51 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…The isotherms were carried out by shaking the MCDBs (0.01 g) with 10 mL of metal ion solution at different initial concentrations. The corresponding adsorption isotherms for lead ions were described by tting the experimental data to the Langmuir, Freundlich, 27 and Temkin isotherms, 28 respectively. The Langmuir equation used was the linear form eqn (6): 29 C e /q e ¼ aC e /K L + 1/K L (6) where q e and C e are the solution (mg g À1 ) and surface concentrations (mg L À1 ) for the adsorbate at the equilibrium, respectively, and K L (L g À1 ) and a (L mg À1 ) are the isotherm constants.…”
Section: Batch Experimentsmentioning
confidence: 99%
“…The isotherms were carried out by shaking the MCDBs (0.01 g) with 10 mL of metal ion solution at different initial concentrations. The corresponding adsorption isotherms for lead ions were described by tting the experimental data to the Langmuir, Freundlich, 27 and Temkin isotherms, 28 respectively. The Langmuir equation used was the linear form eqn (6): 29 C e /q e ¼ aC e /K L + 1/K L (6) where q e and C e are the solution (mg g À1 ) and surface concentrations (mg L À1 ) for the adsorbate at the equilibrium, respectively, and K L (L g À1 ) and a (L mg À1 ) are the isotherm constants.…”
Section: Batch Experimentsmentioning
confidence: 99%
“…(Krysztof, Olejnik et al, 2018) The preparation technology of NMMO/H 2 O regenerated cellulose has been industrialized (Carrick, Pendergraph et al, 2014) and widely used in cellulose-based aerogels,(C. Zhang, Zhai et al, 2017) hydrogels, (Cao, Li et al, 2018) lms, beads, (Hao, Sh et al, 2020) microspheres, (Sw, Yg et al, 2020) laments, and textile fabrics. (Jie Cai, Liu et al, 2012;Jiang, Wang et al, 2017) Korpela et al(Korpela, Kunnari et al, 2017) found that NMMO could dissolve cellulose to enhance the properties of nano cellulose (CNF) lms. NMMO dissolved the cellulose in the composite lms, and the remaining CNF lm was heated and compressed to reduce the porosity of the lm.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from low density and cost, they are renewable and biodegradable. A few studies of the cellulose composites as the adsorbents for the removal of pollutant have been reported. , The powdered shape of such adsorbents might cause difficulty for running the filtration and separation effectively, resulting in the lower potential application in a large-scale water treatment . The exploration of cellulose-based adsorbents which could facilitate the applications in large-scale, such as beads and other shaped particles, is therefore necessary and has been the hot topic for researchers.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 The powdered shape of such adsorbents might cause difficulty for running the filtration and separation effectively, resulting in the lower potential application in a large-scale water treatment. 18 The exploration of cellulose-based adsorbents which could facilitate the applications in large-scale, such as beads and other shaped particles, is therefore necessary and has been the hot topic for researchers. Zhang et al synthesized the magnetic cellulose beads entrapped with activated carbon in an attempt to remove both MB (Methylene Blue) and MO (Methyl Orange).…”
Section: ■ Introductionmentioning
confidence: 99%